Can I touch your hair? : poems of race, mistakes, and friendship - Latham, Irene; Waters, Charles, 1973-; Qualls, Sean; Alko, Selina (Minneapolis, MN : Carolrhoda Books, 2018)
Presents a collection of poems that looks at the experience of race through fifth graders Irene Latham, who is white, and Charles Waters, who is African American.
Pub Weekly, November 2017
Kirkus Starred, October 2017
Booklist, November 2017
4.6
3-6
Keywords: Race awareness -- Poetry; Race relations -- Poetry; Friendship -- Poetry; Poetry; Race awareness; Race relations; Friendship